A structural model with Explicit Distress - Correia, Ricardo; Población, Javier (Journal of Banking & Finance, 2015)
We construct a model for valuing firms and corporate securities incorporating economic and financial distress. The inclusion of financial distress costs is able to explain the low debt/zero debt puzzle and to clarify the relation between earnings and financial leverage. With standard parameter values, this model generates more realistic estimates of leverage ratios, credit spreads and recovery rates relative to a standard model of direct costs of bankruptcy. It clarifies the relation between optimal leverage and debt capacity and addresses different structural model problems such as underestimating (overestimating) spreads on safe (risky) bonds and relying on unrealistic high estimates for direct costs of bankruptcy.